2013
DOI: 10.1007/s00414-013-0840-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-phase postmortem CT angiography: recognizing technique-related artefacts and pitfalls

Abstract: Background and purpose Multi-phase postmortem CT angiography (MPMCTA) is increasingly being recognized as a valuable adjunct medicolegal tool to explore the vascular system. Adequate interpretation, however, requires knowledge about the most common technique-related artefacts. The purpose of this study was to identify and index the possible artefacts related to MPMCTA. Material and methods An experienced radiologist blinded to all clinical and forensic data retrospectively reviewed 49 MPMCTAs. Each angiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 24 publications
4
28
1
1
Order By: Relevance
“…Of note, the viscosity of PP is 24.9 mPa × s at 25°C [22]. We observed no intraluminal discharge in the small intestine or colon, consistent with recent findings [30]. The cause of the significant retroperitoneal fluid content remains unclear, but we assume that this fluid breaks through to the abdominal cavity, as CT revealed that collections in both spaces were connected.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Of note, the viscosity of PP is 24.9 mPa × s at 25°C [22]. We observed no intraluminal discharge in the small intestine or colon, consistent with recent findings [30]. The cause of the significant retroperitoneal fluid content remains unclear, but we assume that this fluid breaks through to the abdominal cavity, as CT revealed that collections in both spaces were connected.…”
Section: Discussionsupporting
confidence: 78%
“…Not unexpectedly, PP leaked into the gastric cavity due to early postmortem autolysis [28,29]. A retrospective review of 49 multiphase CT angiographies performed in fresh human cadavers showed extravasation in the gastric lumen in 55% of cases [30]. In those cases, reperfusion was achieved with paraffinum liquidum, which has a viscosity of 137.3 mPa × s at 25°C [pers.…”
Section: Discussionmentioning
confidence: 99%
“…The only exceptions comprise parts of the cerebral sinus and vessels, which are, in some cases, occluded by huge PM clots, 39 which can create artefacts. A recent study has shown that all artefacts observed after an MPMCTA are reproducible and stable in terms of their localization and type, making them relatively easy to recognize.…”
Section: Today's Most Used Post-mortem Ct-angiography Techniques Multmentioning
confidence: 99%
“…A recent study has shown that all artefacts observed after an MPMCTA are reproducible and stable in terms of their localization and type, making them relatively easy to recognize. 39 Understanding of these artefacts can avoid misinterpretation during the radiological evaluation and therefore increase the quality of the radiological interpretation.…”
Section: Today's Most Used Post-mortem Ct-angiography Techniques Multmentioning
confidence: 99%
“…Some standardized protocols have been developed and published; their application would allow making the procedure more easily reproducible and the operators aware of possible artifacts that its application can generate. In this regard, Bruguier and colleagues [89] have recently published a study in which they have evaluated technique-related artifacts in 54 cases in which the MPMCTA was performed according to the protocol proposed by Grabherr et al [8]. The identification and categorization of these artifacts according to their type, anatomical location, and timing of appearance during the angiography are of utmost importance, because the MPMCTA technique was developed with the aim of applying it in routine forensic investigations.…”
Section: Discussionmentioning
confidence: 98%